Melaleuca armillaris Essential Oil as an Antibacterial Agent: The Use of Mesoporous Bioactive Glass Nanoparticles as Drug Carrier - Ballarre, Josefina (2023)
Bioactive glasses have been proposed for bone tissue engineering due to their excellent biocompatibility and osteo-inductive behaviour. The generation of mesoporous bioactive glass (nano) particles adds a high surface area for the dissolution and release of bioactive ions, and the possibility to load them with different drugs for antibacterial purposes. Essential oils (EO) are an interesting resource for alternative medical therapy, providing antimicrobial compounds that come from organic/natural resources like aromatic plants. Also, a biological polymer, such as chitosan, could be used to control the release of active agents from mesoporous bioactive glass (MBG) loaded particles. This work presents MBG particles with nominal composition (in mol) 60% SiO₂, 30% CaO and 10% P₂O₅, loaded with essential oil of Melaleuca armillaris, which contains 1,8-cineol as the main active component, with an inhibitory in vitro activity against several bacterial species. Also, coloading with a broad-spectrum antibiotic, namely gentamicin, was investigated. The MBG particles were found to be of around 300nm in diameter and to exhibit highly porous open structure. The release of EO from the particles reached 72% of the initial content after the first 24 h, and 80% at 48 h of immersion in phosphate buffered solution. Also, the MBG particles with EO and EO-gentamicin loading presented in vitro apatite formation after 7 days of immersion in simulated body fluid. The antibacterial tests indicated that the main effect, after 24 h of contact with the bacteria, was reached either for the MBG EO or MBG EO-gentamicin particles against E. coli, while the effect against S. aureus was less marked. The results indicate that MBG particles are highly bioactive with the tested composition and loaded with EO of Melaleuca armillaris. The EO, also combined with gentamicin, acts as an antibacterial agent but with different efficacy depending on the bacteria type.